Pendekatan Model Supply Chain Quality Management Terhadap Daya Saing Perusahaan Gula - Wisnu Eko Nugroho; Rida Zuraida (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
The sugar industry has a vital role in Indonesia. However, faces several challenges such as low quality, low productivity and inability to fulfil domestic demand. Certain corrective actions are necessary to make the industry more competitive. The supply chain quality management (SCQM) approach is expected to increase the productivity and competitiveness of sugar industry. This research aimed to formulate an SCQM approach on company competitiveness which suitable for sugar companies and analyze the effect of SCQM to company competitiveness using the structural equation modelling. By using Smart-PLS 4.0, the results showed that 49.1% of company competitiveness is influenced by organizational quality, Organizational quality is influenced by customer focus, supplier quality management, the effectiveness of the IT system, and leadership which are variables of SCQM. The SCQM approach significantly influences the competitiveness of sugar companies in being able to lead the competition, improve product quality, adapt to changes, reduce production costs, and gain loyal customers. Process integration shows a positive influence on organizational quality, which enhances future company competitiveness. Keywords: Competitiveness, quality, structural equation modeling, sugar, supply chain